Two neglected origins of inequality: Hierarchical power and care work - Armanda Cetrulo; Dario Guarascio; Maria Enrica Virgillito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2024)
Are wages really a good proxy of the value of labour? Or, alternatively, do they largely reflect socio-institutional embedded practices of current societies according to which a manager deserves to be paid more than a nurse? This paper studies the determinants of wage remuneration and wage distribution focusing on two neglected origins of inequality: hierarchical power and care-work. Our contributions include, first the construction of a new synthetic indicator able to capture and quantitatively assess the distribution of power across occupations; second, the development of an indicator able to fine grained account for care jobs; third, the econometric estimation of the determinants of wage levels and wage distribution contrasting our new proxies for occupational attributes of care and power versus the benchmark Mincer equation and the routine task index. Our results downplay the role of the accustomed routine task index in determining the wage remuneration and prove the role of the socioinstitutional embeddedness of wage determination, rooted on hierarchical positions and largely discarding the role of essentiality in the executed job activity.
Keywords: J3; J5; M54; 330; Wage determination; social classes; labour-process; managerial functions; care jobs